ANALISIS PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN SAMOSIR - Saniyah Yulandari, Viny (Jurnal Samudra Geografi, 2024)
This research aims to: (1) Determine the distribution of forest and land fires that occur in Samosir Regency, (2) Determine efforts to control forest and land fires by BPBD Samosir Regency, and (3) Determine efforts to control forest and land fires by local communities. The method used is descriptive qualitative with purposive sampling with Key Informant sampling technique. The object of this research is that physical objects can be obtained from observation, secondary data, community interviews. Meanwhile, in terms of social objects, the sample is the Head of the BPBD and the Implementation Team in the field of forest and land fires as well as the emergency sector and the community, such as village heads, village officials and community leaders in areas where forest and land fires have occurred. The results of the research show: (1) The distribution of locations prone to forest and land fires in Samosir Regency is concentrated in two sub-districts, namely: Sianjur Mula-Mula District and Harian District, (2) Efforts to control forest and land fires carried out by BPBD Samosir Regency are quite good, and (3) Efforts to control forest and land fires carried out by the community.